Concurrence of Intraoperative Hypotension, Low Minimum Alveolar Concentration, and Low Bispectral Index Is Associated with Postoperative Death. (October 2015) - Willingham, Mark D.; Karren, Elliott; Shanks, Amy M.; O'Connor, Michael F.; Jacobsohn, Eric; Kheterpal, Sachin; Avidan, Michael S.
<x xml:space="preserve">Abstract</x> Background: An intraoperative concurrence of mean arterial pressure less than 75 mmHg, minimum alveolar concentration less than 0.8, and bispectral index less than 45 has been termed a "triple low" state. An association between triple low and postoperative mortality has been reported but was not replicated in a subsequent study. The authors pooled existing data from clinical trials to further evaluate the purported association in an observational study. Methods: This retrospective observational study included 13, 198 patients from three clinical trials: B-Unaware, BAG-RECALL, and Michigan Awareness Control Study. Patients with greater than 15 not necessarily consecutive minutes of triple low were propensity matched to controls with similar characteristics and comorbidities. A multivariable Cox proportional hazards model was used to evaluate the association between triple low duration and postoperative mortality. Results: Thirty-day mortality was 0.8% overall, 1.9% in the triple low cohort, and 0.4% in the nontriple low cohort (odds ratio, 5.16; 95% CI, 4.21 to 6.34). After matching and adjusting for comorbidities, cumulative duration of triple low was significantly associated with an increased risk of mortality at 30 days (hazard ratio, 1.09; 95% CI, 1.07 to 1.11, per 15 min) and 90 days (hazard ratio, 1.09; 95% CI, 1.08 to 1.11, per 15 min). Conclusion: There is a weak independent association between the triple low state and postoperative mortality, and the propensity-matched analysis does not suggest that this is an epiphenomenon.